Head injury mechanisms in FIS World Cup alpine and freestyle skiers and snowboarders - Steenstrup, S. E.; Bakken, A.; Bere, T.; Patton, D. A.; Bahr, R. (British Journal of Sports Medicine, 2018)
Introduction: Head injuries represent a concern in skiing and snowboarding, with traumatic brain injuries being the most common cause of death.